A new species of Terellia (Diptera: Tephritidae) from Iran with a key to the species of the tarbinskiorum group - Namin, Saeed Mohamadzade; Nozari, Jamasb; Najarpoor, Arezoo (Zootaxa, 2011)
Terellia korneyevorum sp. nov., reared from flower heads of Echinops spp. is described from Iran. It is similar to T. tarbinskiorum Korneyev and T. bushi Korneyev in its mesonotum pattern and male genitalia structure, differing by its narrow, widely separated preapical and apical crossbands. The three species are separated from the quadratula group of species to form a new group; the diagnosis of the tarbinskiorum group of species is given. All the species of this group share presence of three pairs of black shining spots on the scutum, one on the transverse suture, one at the dorsocentral and one at prescutellar acrostichal seta base. They also share such a pattern with the species of Orellia Robineau-Desvoidy 1830, differing by the structure of male genitalia and different host plants. A key to the species of tarbinskiorum group is given.